Recognition of comprehensive income in Slovak companies - Lapková, Marta; Stašová, Jana (Buhalterinės apskaitos teorija ir praktika, 2014)
Financial statements are the key resource for assessing a company´s performance. The form and content of financial statements reflect a country`s accounting regulations. If financial statements can be drawn up under a range of different principles and procedures, this may cause problems for external users. The purpose of this paper is to evaluate comprehensive income recognition in the financial statements of Slovak companies that are prepared according to IFRS, with an emphasis on items of other comprehensive income. Our research showed that Slovak companies preparing financial statements in accordance with IFRS use a range of options allowed by national standards. Therefore the form of their comprehensive income recognition varies. Other comprehensive income was recognized in the statement of profit or loss and other comprehensive income, in the majority of researched entities. Our research shows that reporting of other comprehensive income divided into reclassified and not reclassified items is relevant for the assessment of company performance, because of their impact on reported profit or loss, and on selected indicators of profitability, particularly for our sample of financial institutions. This is due to the nature of their activity, for in most cases the gains and losses on financial assets available for sale are recognized in other comprehensive income, which will be reclassified to profit or loss in subsequent periods.